Strategia rozwoju przedsiębiorstwa na przykładzie firmy Maspex - Wołczek, Przemysław (Growth Strategy of An Enterprise on the Example of Maspex Company, 2006)
The paper describes growth strategy of Maspex company. The analysis of the corporate strategy in view of the area of competitive actions, the type of relations with competitors and the kind of competitive advantage was done. Moreover the author characterized the methods, which are used by the enterprise to grow (internal growth or external growth). Maspex gained the position of one of the largest food industry companies in Middle Eastern Europe. Decisions, which were made in the mentioned strategic areas contributed to this achievement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 387-397